2021
DOI: 10.1111/1348-0421.12947
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines profile in patients with acute and chronic hepatitis B infection

Abstract: Hepatitis B virus (HBV) is one of the leading causes of acute and chronic hepatitis and represents a serious public health threat. Cytokines are important chemical mediators that regulate the differentiation, proliferation, and function of immune cells, with accumulating evidence indicating that the inadequate immune responses are responsible for the elimination or persistence of HBV. This study aimed to determine the cytokine profiles (IFN-γ, TNF-α, IL-2, IL-4, IL-6, IL-10, and IL-17A) during HBV infection an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…The analysis of acute hepatitis A, C, and E cases showed that the mean values of IL-6 in the acute phase were 61.6, 26.3, and 15.5 pg/mL, respectively, and those of TNF-α were 52.3, 22.8, and 61.6 pg/mL, respectively. Interestingly, in all the studies, the serum cytokine concentrations were significantly higher in patients with acute hepatitis than in normal participants [ 19 21 ]. In addition, two reports of Japanese patients with severe acute Epstein–Barr virus or cytomegalovirus infection accompanied by extreme liver dysfunction, described elevated serum IL-6 levels of 7.0 and 10.3 pg/mL, respectively, at the time of admission [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of acute hepatitis A, C, and E cases showed that the mean values of IL-6 in the acute phase were 61.6, 26.3, and 15.5 pg/mL, respectively, and those of TNF-α were 52.3, 22.8, and 61.6 pg/mL, respectively. Interestingly, in all the studies, the serum cytokine concentrations were significantly higher in patients with acute hepatitis than in normal participants [ 19 21 ]. In addition, two reports of Japanese patients with severe acute Epstein–Barr virus or cytomegalovirus infection accompanied by extreme liver dysfunction, described elevated serum IL-6 levels of 7.0 and 10.3 pg/mL, respectively, at the time of admission [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, distorted cytokine expression has been found in acute and chronic hepatitis B patients ( Ribeiro et al, 2022 ). Our study found that CXCL8 was disregulated in HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…In HBV infection, ALT conveys limited information, which can only indicate the liver injury caused by viral factors. However, the result of HBV infection is not only dependent on viral factors, but also related to host factors, such as the immune response of the body ( Ribeiro et al, 2022 ). CXCL8, CXCL9, CXCL10, and CXCL11 can recruit immune cells to the site of inflammation to play a role in clearing pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Viremia lasting for 6 months or more, is considered persistent HCV infection. 115 , 116 HCV uses a variety of methods to evade the immune system, resulting in immune system evasion and infection persistence. 117 T cell function is lost in chronic T cell stimulation, which is the first main mechanism of chronic infection.…”
Section: Immunopathogenesis Of Hcvmentioning
confidence: 99%
“…However, the decline of the CD4 + T cell activity specific to HCV is closely linked to the transition of acute infection of HCV into the chronic HCV infection. 116 Moreover, inadequacy and the subsequent reduction in a strong CD4 + T cell activity following acute infection have been documented and linked to chronic infection. 119 HCV escape mutations for individuals having multiple HLA epitopes (plus the HLA-DRB1*15 epitope) have been hypothesized as one route which decreases the CD4 + T cell activity.…”
Section: Immunopathogenesis Of Hcvmentioning
confidence: 99%